Average daily cooling capacity of radiation conditioning system - V. I. Karagusov; I. N. Pogulyaev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Relevance of the main advantages of radiation cooling is autonomy, i.e. independence of radiation cooling systems from electrical and thermal energy. The operation of radiation life support systems does not require significant costs, either during creation or during operation. The purpose of the study is to determine the possibility of using a radiation cooling system for air conditioning in residential or office premises. The task of the study is to determine the cooling capacity of the radiation air conditioning system. Experimental studies have shown that the radiation conditioning system has a cooling capacity in summer from 4 to 7 kW with a radiation cooler of 100 m2